Persepsi Masyarakat Islam terhadap Agama Kristen (Study Deskriptif Di Labuhan Ruku Kecamatan Talawi Kabupaten Batub Bara) - Hotmaida Ritonga; Corry Corry; Maria S.M Purba (Departement of Mathematics Education, 2023)
This research is entitled Perceptions of Islamic Communities towards Christianity in Labuhan Ruku, Talawi Sub-District, Batu Bara District. In this research, the writer wanted to find out how the relationship between Islamic society and Christian society was, whether it was peaceful and peaceful or whether there was conflict in it. This study aims to examine the religious life of the community in Labuhan Ruku and also to examine the perceptions of Muslims in Labuhan Ruku towards Christians and to examine the impact of this perception on religious life. The research method used in this study is a qualitative research method with a descriptive approach, namely by conducting interviews with the Islamic community living in Labuhan Ruku. This research was conducted in December 2022. Based on the results of the research conducted, it can be concluded that not everything is true, if Muslims and Christians cannot live together without conflict, because in Labuhan Ruku Muslims and Christians can live side by side in peace, harmony and mutual tolerance. Muslims do not regard Christians as enemies and vice versa, problems that occur outside their area such as conflicts between religions do not affect the harmonious relationship between them. If we want to improve relations between Christians and Muslims we must deepen our knowledge. We have to avoid stereotypes, we have to learn more about other religions so that we understand how their lives are and how we can respect each other so that we can coexist together in peace and tranquility